REGIONAL ANGULAR UNCONFORMITIES IN THE CENOZOIC SEQUENCES OF KAMCHATKA - Shapiro M.N.; Gladenkov Yu.B.; Shantser A.E. (My University, 1996)
Several angular unconformities have been recognized in Cenozoic sections of the Kamchatka region located in the Pacific-Asia transition zone. They are of a regional scale and confined to certain levels: the Cretaceous-Paleogene boundary (most likely, of limited extent), and pre-middle Eocene, pre-Pliocene, and, probably, Quaternary levels. These unconformities reflect short-time tectonic events that were accompanied by the formation of three major fold-thrust (or accretionary) zones in Kamchatka.
Keywords: Cenozoic; Cenozoic; Кайнозой